Proposal for a National Interprofessional School of Rural Health - Nixon, G; Bagg, W; Kerse, N; Skinner, M; Crampton, P; Larmer, P (New Zealand Medical Association, 2018)
Shortages of health professionals persist in much of rural New Zealand despite a range of targeted university and professional college initiatives. In response to this a collective of universities, professional colleges and sector groups have put a proposal to Government for a National Interprofessional School of Rural Health. If adopted, this proposal would embed rural health professional education and research in rural communities around New Zealand, empowering them to organise the education that occurs in their community, in a coherent and coordinated way. What is being proposed is not a new or separate education provider but rather an ‘enabling body’ that would lever off the expertise and resources of the existing tertiary institutions, colleges and rural communities. It calls for an ‘all of systems’ approach that encompasses all the health professions that practise in rural areas, undergraduate education and postgraduate training, and rural health research. Although modelled on successful Australian rural clinical schools, it is a uniquely New Zealand solution that is cognisant of the New Zealand context and resources.